Ultrasonic extraction of amaranth oils - Chulak, L. D.; Zadorozhny, V. G.; Chulak, Yu. L.; Chulak, O. T.; Tatarina, O. V. (Journal of Education, Health and Sport, 2018)
The isolation of biologically active substances - extraction, is currently the most difficult and time-consuming task that can be solved only in the conditions of large productions with the help of specialized equipment, and practically impossible at home. As numerous studies show, from the natural raw material of plant and animal origin it is possible to extract practically all known compounds, which are produced by plants [1]. The authors carried out extraction of amaranth in cold pressed olive oil. Since it is close in composition with amaranth oil. The biological activity of the oil is due to the presence of squalene and tocotrienol, and the percentage of their various fractions possessing antioxidant properties.